Study guides

Q: What is x square - y square?

Write your answer...

Submit

Related questions

x=y

If X is the square of Y then Y is a square root of X. But, -Y is also a square root.

x-y=x² only if y = x - x²

They are reverse operations, in the sense that if y is the square of x then x is a square root of y. Remember though, that in the above scenario, -x is also a square root of y.

y = square root of x y = x(1/2) y' = (1/2)x(1/2 - 1) y' = (1/2)x(-1/2) y' = (1/2)(square root of x)

40

You just have to plug in numbers for x and plot it on a graph. You can't have a square root of a negative number, so the graph starts at 0 and moves to the right. You'll have to use a calculator to get the decimal approximation for some of y values. x=0, y=0 x=1, y=1 x=2, y= square root of 2 x=3, y=square root of 3 x=4, y=2 x=5, y=square root of 5 etc...

5

The square root of a number x is one that, when multiplied by itself gives the value x. So if y * y = x then y is the square root of x. But, (-y)*(-y) also equals x. So -y is also a square root of x. Thus, given any positive number, x, there are two numbers, y and -y whose square is x. So both of them are square roots of x. One of y and -y must be greater than 0 and the other must be less than 0. The one that is less than 0 is the negative square root. As an example, 4 * 4 = 16 and (-4) * (-4) = 16 so both, 4 and -4 are square roots of 16. -4 is the negative square root while 4 is the positive square root (also called the principal square root).

X=k/square of y

That can be true when "x" and "y" are both zero, or both 1.

If x equals the square root of ...., then you already have solved for x

(x - y)(x + y)

X^1/2 + Y^1/2 Essentially it is just the square root of x plus the square root of y, there's no real way of simplifying that.

If x is a multiplication symbol, then square root of 36(4)y^2 = square root of(4^2)(2^2)(y^2) = (4)(2)(y) = 8y If it is a variable x, then square root of 36x4y^2 = square root of (4^2)(x)(2^2)(y^2) = (4)(2)(y)(square root of x)= 8y(square root of x)

y = sqrt X + 3sqrt X is the same as y = 4 sqrt X

Square roots of square roots. The fourth root of a number, x, is another number, y such that y*y*y*y = x ie y multiplied by itself 4 times is x.

X + y

x=length of square x multiplied by y = area of square y=width of square width multiplied by length = area

A natural number is y is called perfect square if there exists an integer x such that y=x2

suppose the n has the prime factorization of x*y. We know that every unique integer has a unique prime factorization. n*n = (x*y)*(x*y) = x^2*y^2.

sorry, it is wrong the answer is : y=k/x2(square) {when y = x we will write y as x and leave x2(square) alone. like this: x=120/x2(square) x multiply by x2(square) is x3(cube) so cube root of 120 = x so x is 4.93

Yes, if x and y = 1 √1 + √1 = √1 + 1 1 + 1 = 1 + 1 QED

Yes.

A square root is taking a number X and determining which two same numbers times each other, or Y*Y equal X. If X equals 9, the square root of it is 3; that is 3 (Y) multiplied by 3 (Y) is 9.